2020
DOI: 10.3390/genes11080860
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Genetic Transformation Protocol for Chrysanthemum cv. ‘Jinba’ with TERMINAL FLOWER 1 Homolog CmTFL1a

Abstract: Chrysanthemum (Chrysanthemum x morifolium Ramat.) cultivar Jinba is a distinctive short-day chrysanthemum that can be exploited as a model organism for studying the molecular mechanism of flowering. The commercial value of Jinba can be increased in global flower markets by developing its proper regeneration and genetic transformation system. By addressing typical problems associated with Agrobacterium-mediated transformation in chrysanthemum, that is, low transformation efficiency and high cultivar specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…An increased amount of protein leads to the stagnation of metabolic processes and the death of explants [ 30 ]. Compared with other research results, it was reported that 15–25 mg·L −1 kanamycin completely inhibited callus induction and led to explant browning [ 28 ]. In this study, 10 mg·L −1 kanamycin was the optimal concentration for screening.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…An increased amount of protein leads to the stagnation of metabolic processes and the death of explants [ 30 ]. Compared with other research results, it was reported that 15–25 mg·L −1 kanamycin completely inhibited callus induction and led to explant browning [ 28 ]. In this study, 10 mg·L −1 kanamycin was the optimal concentration for screening.…”
Section: Resultsmentioning
confidence: 88%
“…As previously shown in some studies, Li et al reported that a concentration ratio of 2:1 of cytokinin to auxin was conducive to the formation and differentiation of chrysanthemum leaf explants, while a high concentration of 6-BA (5 mg·L −1 ) and a low concentration of NAA (0.1 mg·L −1 ) were conducive to the induction and differentiation of shoot tip thin-cell-layer explants [ 28 ]. Similarly, Wang et al reported the highest germination rate of ground-cover chrysanthemum on MS medium containing 2.0 mg·L −1 6-BA and 0.5 mg·L −1 NAA [ 29 ].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Constitutive overexpression of CmTFL1a resulted in the delaying of the transition to the reproductive phase and significantly affected plant morphology in chrysanthemum cv. Jinba [ 114 ]. Nakano et al (2020) demonstrated that photoperiodic variations in heat sensitivity fluctuations affected flowering in chrysanthemum, supporting an earlier study wherein heat-induced flowering delay was caused by the suppression of FTL3 expression, suggesting that daily fluctuations in heat sensitivity may correlate with the rhythm of FTL3 regulation [ 115 , 116 ].…”
Section: Flowering Time and Developmentmentioning
confidence: 99%
“…It was reported that the callus of chrysanthemum cultivar 'White ND' could be induced on MS medium supplemented with 1 mg L −1 6-BA and 2 mg L −1 NAA, but it needed to be changed onto medium containing 2 mg L −1 6-BA and 0.5 mg L −1 NAA to continue to differentiate [10]. Furthermore, most reports currently use cultivar 'Jinba' as the material for gene function verification [5,11], but it is a white, double-petaled cut chrysanthemum cultivar, which is not suitable for flower color and flower development research. Therefore, it is important to screen more chrysanthemum cultivars with high regeneration rates and diverse genotypes, and establish an efficient regeneration system for subsequent research.…”
Section: Introductionmentioning
confidence: 99%